Persepsi Siswa Terhadap Mata Pelajaran Matematika (Studi Kasus Siswa Kelas VI SD Negeri 03 Gumay Ulu) - Reza Lestari; Habibi; Syaiful Bastari (Gayaku Publisher, 2024)
Students perceptions of mathematics lessons will definitely vary because they are closely related to the characteristics of each individual student. In general, students who hold positive perceptions of mathematics tend to achieve high or above-average learning outcomes, while those with negative perceptions are likely to achieve low or below-average learning outcomes. The aim of this research is to analyze and test the relationship between students' perceptions of mathematics, especially among class VI students at SD Negeri 03 Gumay Ulu. The subjects of this research were students in classes VI at SD Negeri 03 Gumay Ulu during the 2023/2024 academic year.